Effects of ultrasonic time, size of aggregates and temperature on the stability and viscosity of Cu-ethylene glycol (EG) nanofluids. (February 2019) - Li, Fashe; Li, Long; Zhong, Guijiang; Zhai, Yuling; Li, Zhouhang
Highlights: Effects of ultrasonic time and temperature on viscosity of Cu-EG nanofluids are explored. The viscosity is the lowest under a proper ultrasonic time for all cases. Effects of ultrasonic time, aggregation sizes, temperature on viscosity variations are explained. A new correlation of viscosity as a function of temperature and mass fraction based on experimental data. Abstract: In this work, 50 nm Cu nanoparticles having solid concentration of 1.0 wt%, 2.0 wt% and 3.8 wt% are added to ethylene glycol in the absence of a surfactant. The stability of Cu-EG nanofluids for different ultrasonic times (ranging from 0 to 75 min) is tested. The effect of temperature on viscosity is also investigated for an optimum ultrasonic time. However, effects of ultrasonic time, size of aggregates and temperature on viscosity variation have not yet been studied in detail. The results show that, with the increase in ultrasonic time, the viscosity of Cu-ethylene glycol (EG) nanofluids firstly decreases up to an optimum time, after which, it increases gradually. The viscosity always decreases with the increase in temperature. Furthermore, higher mass fraction results in shorter ultrasonic time. An optimum ultrasonic time at which the viscosity is the lowest is determined. With the increase in ultrasonic time and temperature, the Brownian motion intensifies and big clusters (aggregates of nanoparticles) are broken up. Smaller clusters cause low flow resistance in nanofluids, thereby resulting in low viscosity. However, excess ultrasonic energy coalesces them to again form larger clusters due to high surface energy. Finally, a regression correlation for viscosity as a function of temperature and mass fraction is presented based on the experimental data.